2017
DOI: 10.1002/bit.26331
|View full text |Cite
|
Sign up to set email alerts
|

Production of zebrafish cardiospheres and cardiac progenitor cells in vitro and three‐dimensional culture of adult zebrafish cardiac tissue in scaffolds

Abstract: The hearts of adult zebrafish (Danio rerio) are capable of complete regeneration in vivo even after major injury, making this species of particular interest for understanding the growth and differentiation processes required for cardiac tissue engineering. To date, little research has been carried out on in vitro culture of adult zebrafish cardiac cells. In this work, progenitor-rich cardiospheres suitable for cardiomyocyte differentiation and myocardial regeneration were produced from adult zebrafish hearts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In order to resolve this problem, primary adult cardiomyocytes ( Sander et al, 2013 ) and cardiospheres ( Zeng et al, 2017 ) from the zebrafish heart have been cultured successfully. Yet these systems lack the context of an injury, maturity of cardiomyocytes and the complexity of other cell types present in the heart.…”
Section: Introductionmentioning
confidence: 99%
“…In order to resolve this problem, primary adult cardiomyocytes ( Sander et al, 2013 ) and cardiospheres ( Zeng et al, 2017 ) from the zebrafish heart have been cultured successfully. Yet these systems lack the context of an injury, maturity of cardiomyocytes and the complexity of other cell types present in the heart.…”
Section: Introductionmentioning
confidence: 99%
“…This alteration was more constant in the fish with higher age (2 and 3 years old). An increase in FBS concentration may introduce trophic factors that are essential for fish cardiac cell proliferation (Zeng et al 2017) and the fish with high age are more sensitive to this alteration compared to low age fish. Previous study on zebra fish showed that the increase in FBS concentrations led to cardiac cell proliferation and development (Zeng et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in FBS concentration may introduce trophic factors that are essential for fish cardiac cell proliferation (Zeng et al 2017) and the fish with high age are more sensitive to this alteration compared to low age fish. Previous study on zebra fish showed that the increase in FBS concentrations led to cardiac cell proliferation and development (Zeng et al 2017). Also, the present study showed that contraction frequencies over time were different (data not showed), that may be due to the change in the supply of growth factors as it occurs when the medium is changed (Grunow et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish are tropical fish that have recently emerged as a new and attractive model for studying physiological and pathological processes, and this is because of its high similarity to the human genome, transparent embryos and suitable for genetic manipulation 6,7 . The zebrafish animal model has been established as a disease model for cardiovascular diseases, and this is because of the fact that adult humans suffer from a high rate of cardiovascular diseases 8 . To date, there are several challenges posed in establishing the heart disease models in zebrafish, limiting their use in this field 9 .…”
Section: Introductionmentioning
confidence: 99%